VALIDITAS BAHAN AJAR BERBASIS RISET PADA MATERI SISTEM REPRODUKSI SMA/MA - Yulia Yulia (Horizon, 2021)
This research is motivated by the limited material in printed books, the book is distributed to students one book for two people and distributed when the learning process is only in school, this makes the learning process very ineffective, for that students need additional teaching materials, especially reproductive system material at school. contraceptive method sub material in the family planning (KB) program. Research conducted in February 2020 aims to produce valid teaching materials for the reproductive system of SMA / MA. The method used in this research is the 4-D model method. Data analysis was carried out by descriptive method. The instrument used in this study was a validity test questionnaire, which was conducted by 3 expert validators, namely 2 lecturers and 1 teacher. The results obtained from the validity test showed a validity value of 86, 9% with very valid criteria because it was in accordance with the content standards, basic competencies and core competencies that had been set.